Improperly figure of speech as the syntactic means of expression the emotivity in football blog and comments - Ulyanova M. A. (Education and science in the modern context, 2016)
the article is devoted to studying the syntactic means of expression emotivity in football blog and comments. The analysis seeks to consider the frequency of use of syntactic means. The relevance of this study is defined, firstly, by the development of the genre of online discourse, like a blog, in particular football blogs, and secondly, by the issue of insufficient knowledge of the syntactic means expressing emotivity in football blogosphere. A study is carried out by a continuous sampling method, the method of contextual analysis, comparative and quantitative methods.
Keywords: риторический вопрос; rhetorical question; эмотивные синтаксемы; риторическое восклицание; риторическое обращение; emotive syntaxemes; rhetorical exclamation; rhetorical appeal